An exploration of strategies employed in English additional language, large class secondary school in Maseru, Lesotho. - Senekane, Mina Mary (My University, 2010)
Large classes are a reality in many schools in developing countries and while most research tend to focus on higher institutions of learning there seems to be paucity of research in secondary schools. In order to add to the existing research in developing countries, this study investigates the classroom management and instructional challenges that English Additional Language (EAL) teachers of a secondary school in Maseru, Lesotho, face in large classes of about 50-60 learners and the strategies they employ to achieve specific outcomes in the English classroom. The study is informed by the Malawi Institute of Education (1997) and research of such authors as Nolasco and Arthur (1988), Carbone (1999), Ives (2000), Xu (2001), Visano (2003), Kolo and Francis (2005) and Benbow et al. (2007) who show that teachers face different challenges in large classrooms. Drawing on the qualitative research design, the data for this study was collected by lesson recordings and follow-up interviews with the teacher-participants. The study shows that the teacher-participants experienced various management and instructional challenges. The most salient management challenges are noise interference, inability to remember and use students‘ names, difficulty in managing behavioural problems and the abuse of mobile phones in the classroom. Some of the instructional challenges include inadequate time to help learners on an individual basis, insufficient time to enhance qualitative input and a lack of classroom and school resources. Some of the strategies the teachers employ to address these challenges include setting rules and procedure for learners, immediate teacher response to behavioural problems, repeating students‘ responses, engaging students in group activities and providing additional or remedial classes. The study concludes that the challenges that teachers experienced in classes that have been defined as large are more than individual teachers can handle. Therefore collective effort from all stakeholders in education is needed. Actively involving students in classroom activities and the use of group discussions seems to be effective strategies that could be used. However, these strategies may not be peculiar to large classes but to average and even small classes. The study recommends that professional development for iv teachers in the form of workshops be offered by the education authorities and teachers share ideas in their individual schools.